Analisis Tingkat Kesulitan Soal Pemecahan Masalah Dalam Buku Siswa Pelajaran Matematika Peminatan SMA Kelas X Kurikulum 2013 - Yulianto, Rismawan; Idris Harta,, Idris Harta, M.A, Ph.D (2017)
This study aims to determine the level of difficulty of problem solving items in mathematics books for grade X of high school students of "peminatan" program of curriculum 2013. The research method is qualitative. The data in this study are solving problems that are analyzed according to the type and characteristics of question containing the type of number, type and use of surgery, a lot of questions, the adequacy of the data, and the similarities problem. The data collected by content analysis of the book. Data analysis technique are by data reduction, data presentation, and conclusion. The results show that: 1) There are 40 items troubleshooting of the whole matter in the book, 2) are 97,50% types of problems routine troubleshooting and 2,50% type of non-routine problem solving, 3) In each question troubleshooting use this type of count numbers are 45%, combined with other types of numbers as negative numbers are 5%, decimals are 40%, and fractions are 10%, 4) Adequacy of data in a question of a complete count, and there are some questions that are similar to the previous problem. From the analysis on problem solving can be summed up in the general level of difficulty about. The percentage of the level of difficulty of questions in categories easily by 17,50%, the categories being is 57,50%, and 25% are difficult category. The percentage of students math books including proportions good about the difficulty level. Keywords: the difficulty level of questions, problems solving, textbook